2019
DOI: 10.1111/oik.05849
|View full text |Cite
|
Sign up to set email alerts
|

The interplay among intraspecific leaf trait variation, niche breadth and species abundance along light and soil nutrient gradients

Abstract: It is assumed that widespread, generalist species have high phenotypic variation, but we know little about how intraspecific trait variation (ITV) relates to species abundance and niche breadth. In the temperate rainforest of southern Chile, we hypothesized that species with wide niche breadth would exhibit 1) high among‐plot ITV, 2) a strong relationship between trait values and the environment, and 3) a close fit between traits and local environment trait optima. We measured leaf functional traits (leaf area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 47 publications
(71 reference statements)
1
23
0
Order By: Relevance
“…Trait-based approaches of species niches that span entire geographical ranges should promote an understanding of how traits determine range limits. Given that we found that greater intraspecific trait variation in wood density, leaf longevity and seed N:P extends niche widths, an important next step is to determine whether range-wide variation in these traits arises from genetic differentiation or phenotypically plastic responses to environmental gradients (Fajardo & Siefert, 2019;Sides et al, 2014;Violle et al, 2012;Yang et al, 2018). Given that we found that greater intraspecific trait variation in wood density, leaf longevity and seed N:P extends niche widths, an important next step is to determine whether range-wide variation in these traits arises from genetic differentiation or phenotypically plastic responses to environmental gradients (Fajardo & Siefert, 2019;Sides et al, 2014;Violle et al, 2012;Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trait-based approaches of species niches that span entire geographical ranges should promote an understanding of how traits determine range limits. Given that we found that greater intraspecific trait variation in wood density, leaf longevity and seed N:P extends niche widths, an important next step is to determine whether range-wide variation in these traits arises from genetic differentiation or phenotypically plastic responses to environmental gradients (Fajardo & Siefert, 2019;Sides et al, 2014;Violle et al, 2012;Yang et al, 2018). Given that we found that greater intraspecific trait variation in wood density, leaf longevity and seed N:P extends niche widths, an important next step is to determine whether range-wide variation in these traits arises from genetic differentiation or phenotypically plastic responses to environmental gradients (Fajardo & Siefert, 2019;Sides et al, 2014;Violle et al, 2012;Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although species-mean trait values (which reflect the general phenotype across a species' geographical range) should relate to species niches, greater intraspecific trait variation also allows populations to grow in a broader range of environments, thereby extending niche widths (Fajardo & Siefert, 2019;Violle et al, 2012;Violle & Jiang, 2009). Positive relationships between intraspecific trait variation and niche widths result from phenotypic plasticity or adaptive trait differentiation between populations, both of which can increase the range of environmental conditions where population growth is positive (see Violle et al, 2012 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…However, these interpretations should be considered carefully since changes in δ 15 N could be influenced by additional factors and our mechanistic understanding of the drivers of δ 15 N variation is still underdeveloped (Evans ). Furthermore, this result indicates that local‐scale (i.e., within population) environmental gradients, that frequently go unmeasured, are very important for determining trait distributions (Fajardo and Siefert , ).…”
Section: Discussionmentioning
confidence: 99%
“…A further consequence of the observed idiosyncratic trait covariance patterns across species is that species would respond differentially to potential climatic changes. Those species with trait covariance patterns that track the environmental changes would have better chances to succeed, given that their trait variation will allow them to tolerate broader range of conditions, while species with a trait covariance that does not follow the climatic changes will exhibit a more restricted capacity to tolerate climatic changes (see Fajardo and Siefert ). Similar ideas have been discussed previously by Laughlin and Messier () as dynamic adaptive landscapes and these could be readily applied in future studies in combination with demographic data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation